Reintegrative justice in practice [ the informal management of crime in an island community - Miles, Helen; Raynor, Peter (Welfare and society, 2014)
This book provides a unique study of the practice of traditional reintegrative community justice in a European society, the Parish Hall Enquiry (PHE) in the Channel Island of Jersey. This is an ancient institution, based on an informal hearing and discussion of a reported offence with the alleged offender and other interested parties, carried out by centeniers (honorary police officers elected to one of Jersey's twelve parishes). Helen Miles and Peter Raynor's research, arising from direct observation, contributes to the literature on 'what works' in resolving conflicts and influencing offenders, and their detailed case studies give a 'hands on' flavour of the process.